Increasing interest in learning tajweed for children through digital learning media - Muhammadong; Mubarok; Rizqi Ali Husein Zulaini; Riansyah Atmana Ruhuputty; Arkam Lahiya (Institute of Computer Science (IOCS), 2023)
Religious education is a vital component of a child's education because it promotes moral and intellectual development. Tajweed is the study of how to properly and accurately comprehend the Quran in accordance with predetermined rules. Some children may struggle to comprehend the tajweed material presented by the teacher. This study therefore proposes a solution for tajweed science based on the use of digital learning media to increase children's interest in studying tajweed through a more engaging and enjoyable approach. Study purpose’s to determine whether the use of digital learning media to construct learning media can increase children's interest in learning tajweed in order to produce research contributions in this area. The implications of research with digital learning materials for tajweed science can provide a more engaging visual representation of the material, enhance student comprehension, and offer more contemporary and effective learning options. The test results indicate that the tajweed digital learning media has an attractive visual appearance, which can attract students' attention to learn tajweed and improve students' comprehension, particularly in terms of the distinction between nun mati and tannins, pronunciation in the law of izhar, pronunciation in the law of idgham, and pronunciation in the law of iklab.